Los derechos de preferencia (vorzugrecht) a propósito del conflicto de derechos de transmisión entre la FPF y algunos clubes de fútbol - Mendoza Del Maestro, Gilberto (2023)
Contracts with preference clauses are agreements adopted by the parties to voluntarily continue to be bound at the end of the contract, with either party unilaterally exercising the right to enter into a new contract. Currently, the Federación Peruana de Fútbol has problems with certain clubs in the framework of transmission rights contracts containing this type of clauses.This paper will address the following points.First, we will explain what are the preference rights and how they are configured. Next, we will analyse the concept of ‘tacit representations’ in relation to pre-emptive covenants. Finally, we will frame the two previous points in the case of the Federation in order to understand the problems that revolve around the contracts that regulate transmission rights.